Florida Solid and Hazardous Waste Regulation Handbook: Local Government Structuring - Michael T. Olexa; Aaron Leviten; Kelly Samek (EDIS, 2004)
The laws of local governments are called ordinances. These local laws have the authority of the state behind them and you can be prosecuted for violating them, much the same as state laws. Local governments have procedural protections similar to those of the state, but these may vary among the local governments. The legislature can also affect local policy and issues through the passage of special laws that apply only to a certain locale. This is EDIS document FE456, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, UF/IFAS, University of Florida, Gainesville, FL. Published December 2003.